Hubungan Hubungan pengetahuan dan pendidikan ibu dengan pemeriksaan iva test pada wanita usia subur dipuskesmas telaga dewa kota bengkulu tahun 2024: Hubungan pengetahuan dan pendidikan ibu dengan pemeriksaan iva test pada wanita usia subur dipuskesmas telaga dewa kota bengkulu tahun 2024 - Rely Novetriyani, Reri Purwitasari (JURNAL BESUREK JIDAN, 2024)
One of the easiest ways to detect cervical cancer early is through Visual Acetic Acid/IVA test, Bengkulu City Health Office Profile Data in 2023, from 113,455 women of childbearing age, only 678 people underwent IVA test, the number of positive IVA tests was 6 people (0.07%) from 20 Health Centers in Bengkulu City, The purpose of this study was to determine the relationship between knowledge and education towards IVA test examination in women of childbearing age (WUS) at the Telaga Dewa Health Center in Bengkulu City in 2024. The type of research used in this study is quantitative with a cross-sectional research design to determine the relationship that influences WUS to undergo the IVA test examination in the Telaga Dewa Health Center area, Bengkulu City. The results There is a relationship between the level of education of women of childbearing age (WUS) and IVA examinations with a value of p = 0.027 (p <0.05), then the level of knowledge shows that there is no relationship between the level of knowledge of women of childbearing age (WUS) and IVA examinations with a value of p = 0.071 (p> 0.05). It is recommended that the Telaga Dewa Health Center, Bengkulu City, can improve education about the importance of conducting IVA examinations for women of childbearing age (WUS) at the Telaga Dewa Health Center.